Effect of moderate-intensity exercise bouts lasting - Karani Magutah; Nilesh B Patel; Kihumbu Thairu (BMJ Open Sport & Exercise Medicine)
Background Sedentary lifestyles and related morbidities are rising among adults despite existing exercise recommendations. Appealing exercise regimes yielding similar/better body composition should be sought.Objective We investigated the effect of moderate-intensity exercise bouts of <10 min on body composition in previously sedentary adults.Methods This unblinded study enrolled 53 healthy sedentary volunteers aged ≥50 years, randomised into one of two gender-balanced exercise interventions: (1) male and (2) female short-duration bouts (MS, n=14; FS, n = 13), and (3) male and (4) female long-duration bouts (ML, n=13; FL, n=13). Short-duration bouts entailed 5–10 min of jogging thrice daily; long-duration bouts, 30–60 min 3–5 days weekly. Body composition was determined at recruitment and 8-weekly thereafter, for 24 weeks.Results At baseline, 14.3% of MS, 38.5% of ML, 92.3% of FS and 69.2% of FL were obese, dropping to 7.1%, 15.4%, 61.5% and 30.8%, respectively. For waist:height ratio, 64.3 % of MS, 76.9% of ML, 100% of FS and 84.6.3% of FL had ratios >0.5, dropping to 42.9%, 30.8%, 92.9% and 26.2%, respectively. While baseline MS and ML waist:hip ratio (WHR) ≥0.9 were 64.3% and 69.2%, respectively, they correspondingly dropped to 23.1% and 21.4%. The FS and FL with WHR ≥0.85 dropped from 46.2% to 15.4% and from 30.8% to 7.7%, respectively. Body composition variables improved for both sexes (all p <0.05) and mean change between exercise regimes was comparable for both sexes.Conclusion In equal cumulative times, moderate-intensity exercise bouts lasting <10 min are comparable with current 30–60 min bouts in body composition modification for adults of ≥50 years.